Assessing the impact of high-yielding varieties of maize in resettlement areas of Zimbabwe - Bourdillon, Michael; Hebinck, Paul; Hoddinott, John F.; Kinsey, Bill; Marondo, John; Mudege, Netsayi; Owens, Trudy (International Food Policy Research Institute, 2003)
This study is part of a larger effort to explore the impact of agricultural research on poverty reduction. It examines the diffusion and impact of hybrid maize in selected resettlement areas of rural Zimbabwe, paying particular attention to varieties made widely available from the mid-1990s onwards. While "Zimbabwe's Green Revolution" of the early 1980s was characterized by the widespread adoption of hybrid maize varieties and significant increases in yields, the subsequent diffusion of newer varieties occurred more slowly and had a more modest impact. Several factors account for this. Government now plays a much-reduced role and one that increasingly focuses on "better farmers." Private-sector institutions that have entered the maize sector operate mainly in areas of high agricultural potential. Consequently, "adoption" partly reflects "choice" but also the (sometimes) limited physical availability of varieties. A further factor is the nature of the technology being introduced. Newer varieties are bred to meet the evolving needs of commercial farmers, but these new needs -- most notably improved disease resistance -- are not shared by the farmers in our survey and are not associated with significantly higher yields where use of fertilizers is limited. A further consideration is that information is disseminated via multiple channels and in a fragmentary fashion in an environment where tolerance of dissent is limited, the behavior of neighbors is viewed suspiciously and some actors involved in dissemination (such as extension workers) are increasingly viewed with mistrust. The presumption that farmers "learn from each other" is less applicable in circumstances such as these. Our case studies indicate links between the production of maize in excess of subsistence needs, the accumulation of assets such as livestock and tools, payment of school fees, and the acquisition of inputs such as fertilizer and labor for the subsequent cropping season. This coincides with the views of farmers who see high-yielding varieties of maize as an influential factor in raising livelihood above the level of poverty that prevailed when they first moved into the area. However, new varieties appear to have increased incomes only marginally. When we control for farmer characteristics and the endogeneity of adoption, use of these new varieties increases crop incomes only by about 10 percent; a 10-percent increase in maize income is associated with an increase in livestock holdings ranging from 4 to 12 percent. However, these modest impacts result in an improved ability to deal with vulnerability. Hybrids do raise productivity in maize production. Higher income from maize, and from other crops, leads to investment in livestock. And livestock holdings are an important means through which child health is protected when drought occurs. All such changes are associated with an improvement in well-being and a reduction in poverty